The Effects of Route Optimization Software to the Customer Satisfaction - Muhammed Faik Kaya; Ali Durdu (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Route optimization, which is a result of the advancement of technology today, makes companies profitable within months. The aim of this study is to explain the relation between route optimization software and the customer satisfaction. Route optimization softwares become widely used by the companies and this study touches briefly on the subject of the relation between route optimization software and customer satisfaction level. While explain this relation, the study described route optimization software, how it works and its execution areas. Hereafter, the article start to explain customer satisfaction and route optimization software’s effects on customer satisfaction and conclude the study. In the drafting and writing process of this article, the topic is detaily searched and analyzed.